Consideration of stakeholder interests in the planning of sustainable waste management programmes - López-Toro, Alberto Antonio; Rubio-Romero, Juan Carlos; Suárez-Cebador, Manuel; Arjona-Jiménez, Rafael (Sage, 2016)
Those responsible for developing sustainable solid waste management programmes must consider the impacts of programme elements on everyone involved. This paper focuses on identifying the effects of waste management activities and assessing their overall impact on stakeholders. Collaborating with four focus groups and 36 experts, 19 effects were identified and nine questionnaires were designed to evaluate them, one for each stakeholder group. All told, 1805 people took part in the survey. The results show that the effects most important to the survey participants are: (a) recycling solid urban waste, (b) pollution and (c) corporate social responsibility.
https://openpolicyfinder.jisc.ac.uk/id/publication/9567
Keywords: Residuos - Eliminación; Gestión de residuos; Evaluación del impacto ambiental; Municipal solid waste; Stakeholders; Waste management effects; Impact assessment; Sustainable waste management